PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI BILANGAN PECAHAN - Wulan, Desti Nurul (2013)
The research was motivated by several issues including: (1) learning is still dominated by the teacher. Students are not accustomed to be involved in working on the board, interact with friends in cooperative, filed opinions and ask; (2) The material has not been submitted in contextual learning and the methods used are still conventional., (3) student learning outcomes in the material fractions sum still many under the KKM. The purpose of this study was to determine the planning and implementation of learning the material fractions using CTL approach and to improve student learning outcomes in the material fractions using CTL approach in the fourth grade students of SDN Inpres Cikahuripan, Lembang. CTL approach is an approach that helps teachers relate what is taught to the real situation of students and to encourage students to make connections between the knowledge possessed by its application in their lives as members of families and communities. The research method used was Classroom Action Research (CAR), which was implemented in three cycles. The observations are the subject of the fourth grade students of SDN Inpres Cikahuripan as many as 23 students. The results obtained showed an increase in student learning outcomes in each cycle. The results in the first cycle average of student learning outcomes is equal to 71.7 (43.5% of students achieving scores KKM), the second cycle gained an average of 78.5 student learning outcomes (60.9% of students achieving scores KKM), and the third cycle was obtained average of 84.8 student learning outcomes (86.9% of students achieving scores KKM). Based on data analysis results obtained in the field, it can be concluded that the approach to learning with CTL on the subject of fractions improve student learning outcomes in class IV A SDN Inpres Cikahuripan Lembang West Bandung Regency. CTL approach can thus be used as a tool to improve student learning outcomes in the material fractions in fourth grade elementary school. Keywords: Contextual Teaching and Learning, Learning Outcomes, Fractions. Penelitian ini dilatar belakangi oleh beberapa permasalahan diantaranya: (1) Pembelajaran masih didominasi oleh guru. Siswa tidak terbiasa dilibatkan dalam pengerjaan soal di papan tulis, berinteraksi dengan temannya secara kooperatif, mengajukan pendapat dan bertanya; (2) Materi pembelajaran belum disampaikan secara kontekstual dan metode yang digunakan masih konvesional.; (3) Hasil belajar siswa pada materi penjumlahan bilangan pecahan masih banyak yang berada dibawah KKM. Tujuan penelitian ini adalah untuk mengetahui perencanan dan pelaksanaan pembelajaran dalam materi bilangan pecahan dengan menggunakan pendekatan CTL serta untuk meningkatkan hasil belajar siswa pada materi bilangan pecahan dengan menggunakan pendekatan CTL pada siswa kelas IV SDN Inpres Cikahuripan, Lembang. Pendekatan CTL adalah pendekatan yang membantu guru mengaitkan materi yang diajarkan dengan situasi nyata siswa serta mendorong siswa untuk membuat hubungan antara pengetahuan yang dimiliki dengan aplikasinya dalam kehidupan mereka sebagai anggota keluarga dan masyarakat. Metode penelitian yang digunakan ialah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam tiga siklus. Subjek penelitannya adalah siswa kelas IV A SDN Inpres Cikahuripan sebanyak 23 siswa. Hasil penelitian yang diperoleh menunjukkan peningkatan hasil belajar siswa pada setiap siklusnya. Hasil penelitian pada siklus I rata-rata hasil belajar siswa yaitu sebesar 71.7 (43.5% skor siswa mencapai KKM), pada siklus II diperoleh rata-rata hasil belajar siswa sebesar 78.5 (60.9% skor siswa mencapai KKM), dan pada siklus III sebesar diperoleh rata-rata hasil belajar siswa sebesar 84.8 (86.9% skor siswa mencapai KKM). Berdasarkan analisis data hasil penelitian yang diperoleh di lapangan maka dapat disimpulkan bahwa pembelajaran dengan pendekatan CTL pada pokok bahasan bilangan pecahan meningkatkan hasil belajar siswa di kelas IV A SDN Inpres Cikahuripan Lembang Kabupaten Bandung. Dengan demikian pendekatan CTL dapat dijadikan sebagai alat bantu untuk meningkatkan hasil belajar siswa pada materi bilangan pecahan di kelas IV sekolah dasar. Kata Kunci : Contextual Teaching and Learning, Hasil Belajar, Bilangan Pecahan.